Dampak korupsi dan politik uang terhadap kualitas demokrasi dan kesejahteraan ekonomi bangsa - Aini, Nisa Nuril (Maliki Interdisciplinary Journal, 2026)
Since the reform era, Indonesia has been committed to realizing popular sovereignty through a transparent democratic system. However, democratic consolidation currently faces serious challenges due to the prevalence of systemic corruption and money politics. This study aims to analyze the impact of damaged political integrity on the quality of democracy and national economic welfare using a literature study method. The results indicate that money politics has reduced the essence of democracy to a mere procedural formality and created elite dominance that erodes public trust. Economically, corruption triggers inefficiency in state resource allocation and hampers Foreign Direct Investment (FDI) due to the high risk of unexpected costs. As a solution, structural reforms are required by strengthening the independence of election management bodies, party funding transparency, and the internalization of economic democracy principles as mandated by Article 33, paragraph (4) of the 1945 Constitution. Collaborative efforts between strengthening civil capacity and technological adaptation are essential to realizing high-integrity governance for inclusive public welfare.